(Un)conventional monetary and fiscal policy - Jing Cynthia Wu; Yinxi Xie (Bank of Canada, 2023)
We build a tractable New Keynesian model to study four types of monetary and fiscal policy. We find that quantitative easing (QE), lump-sum fiscal transfers, and government spending have the same effects on the aggregate economy when fiscal policy is fully tax financed. Compared with these three policies, conventional monetary policy is more inflationary for the same amount of stimulus. QE and transfers have redistribution consequences, whereas government spending and conventional monetary policy do not. Ricardian equivalence breaks down: tax-financed fiscal policy is more stimulative than debt-financed policy. Finally, we study optimal policy coordination and find that adjusting two types of policy instruments-the policy rate together with QE or fiscal transfers-can stabilize three targets simultaneously: inflation, the aggregate output gap, and cross-sectional consumption dispersion.
Keywords: E; E4; E61; E62; E63; 330; Monetary policy; Fiscal policy